Gambaran Figur Otoritas terhadap Kepatuhan Perawat dalam Implementasi Standar Prosedur Operasional Kebersihan Tangan - Amira Maulida Putri (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Background: Nurses’ obedience in the implementation of Standard Operational Procedures of hand hygiene is an effort in preventing phlebitis in the hospital. Report on surveillance data by Infection Prevention and Control or Pencegahan dan Pengendalian Infeksi (PPI) RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro 2017 mentioned the incidence of phlebitis in the Inpatient Installation reached 2.73%. One cause of high rates of phlebitis is incorrect nurse’s hand-washing technique according to the procedures.Aims: This study aimed to analyze the relationship between status of location from RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro, personal responsibility, legitimacy, status, and proximity of authority figures and nurses’ obedience to Standards Operational Procedures of hand hygiene before and after intravenous installation.Method: This study was an analytical study with a cross-sectional framework. This study was conducted in April 2018 at in-patient installation of RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro by inviting 52 nurses chosen with stratified random sampling.Results: It was found that there was a significant correlation between personal responsibility (p = 0.020), status (0.015) and proximity of authority figure (p = 0.000) and nurses’ obedience to the implementation of Standard Operational Procedures of hand hygiene before and after intravenous installation in in-patient installation of RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro.Conclusion: It can be concluded that the majority of the nurses did not follow hand hygiene stages well. The hospital needs to improve nurses’ personal responsibility, authority figure status, and rapport of authority figure.Keywords: hand hygiene, nurse obedience, Standard Operational Procedures